Strategi Dalam Penyediaan Air Bersih Dan Sanitasi Layak Di Desa Labuan Bajo Kecamatan Komodo Kabupaten Manggarai Barat - Ferdinandus Hadur; Kendry Muliyanto; Anggraeny Puspaningtyas (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
This study aims to examine the strategies implemented by the Regional Drinking Water Company (PDAM) in providing adequate clean water and sanitation services in Labuan Bajo Village, Komodo District, West Manggarai Regency. The results indicate that PDAM possesses several strengths, weaknesses, opportunities, and threats in carrying out its functions. The main strengths of PDAM include an extensive distribution network, strong regulatory support, adequate technical capacity, stable availability of raw water, and responsive services. However, its weaknesses include aging infrastructure, limitations in human resource management, financial constraints, the long distance of raw water sources from the distribution center, and frequent service disruptions. The opportunities that PDAM can leverage include regulatory support from the government, increased public awareness of the importance of clean water, the implementation of innovative projects, partnerships with the private sector, and the adoption of modern technology. On the other hand, threats faced by PDAM include the impact of climate change on raw water availability, limited water resources, suboptimal human resource management, and issues with cash flow and long-term funding.By understanding these factors, PDAM can formulate more effective strategies to enhance its performance and provide better clean water and sanitation services. Several recommendations are proposed, including infrastructure revitalization, improved staff training and development, diversification of funding sources, adoption of innovative technologies, and strengthening collaboration with external partners. Implementing these recommendations is expected to support the sustainability of PDAM Labuan Bajo's services in meeting the community's needs for clean water and sanitation in the region.